Correlation Between Reduced IL-1β Levels in Acne Lesions and the Decrease in Acne Inflammatory Lesions Following Topical Vitamin D Administration: A Double-Blind Randomized Controlled Trial - Dahlan NH; Sitohang IBS; Indriatmi W; Wibowo H; Enggy LE (Dove Medical Press, 2024)
Nelly Herfina Dahlan,1,* Irma Bernadette S Sitohang,1,* Wresti Indriatmi,1 Heri Wibowo,2 Liani Elisabeth Enggy3 1Department of Dermatology and Venereology, Faculty of Medicine, University of Indonesia, Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia; 2Department of Integrated Laboratory, Faculty of Medicine, University of Indonesia, Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia; 3Faculty of Medicine, Hasanuddin University, Makassar, Indonesia*These authors contributed equally to this workCorrespondence: Irma Bernadette S Sitohang, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Indonesia, dr. Cipto Mangunkusumo Hospital, Jalan Salemba Raya No. 6, Jakarta, 10430, Indonesia, Email irma_bernadette@yahoo.comBackground: The inflammatory process in acne vulgaris (AV) is characterized by the upregulation of specific pro-inflammatory cytokines, including interleukin (IL)-1β, IL-6, and IL-8, within sebocytes and keratinocytes. Sebocytes have been identified as target cells for bioactive vitamin D. Experimental studies on animal models have demonstrated the potent comedolytic effects of topical vitamin D. However, further research is required to specifically evaluate the impact of vitamin D on inflammatory lesions in acne vulgaris (AV).Objective: To evaluate the effectiveness of topical vitamin D in treating acne vulgaris (AV) lesions by investigating its anti-inflammatory effects on pro-inflammatory cytokine modulation, specifically assessing the correlation between IL-1β levels in acne lesions and the reduction in AV severity.Materials and Methods: This study is a double-blind, randomized, placebo-controlled clinical trial with a 2-arm design over an 8-week intervention period. Participants were randomly assigned to either the topical vitamin D group (cholecalciferol 50 mcg) or the topical placebo group, with each group comprising 32 subjects. All participants received concomitant treatment with topical adapalene 0.1%. Cytokine levels within acne lesions were assessed using Luminex Polystyrene Screening Assays to detect and quantify IL-1β levels. The effectiveness of the treatment was evaluated by monitoring the reduction in the number of inflammatory lesions, while the safety of topical vitamin D was assessed by documenting and analyzing any reported side effects.Results: The study found a significant correlation between the reduction in IL-1β levels within acne lesions and the decrease in moderate and severe inflammatory lesions in acne vulgaris (p = 0.028). The topical application of vitamin D led to a significant reduction in inflammatory AV lesions (p = 0.045). No significant topical side effects were observed in either the vitamin D or placebo groups.Conclusion: This study demonstrates that the topical administration of vitamin D in acne vulgaris (AV) lesions is effective in reducing pro-inflammatory cytokine levels within acne lesions and in decreasing the severity of AV.Trial Registration: NCT05758259. September 5, 2022.Keywords: acne vulgaris, topical vitamin D, IL-1β, Luminex